Clinical characteristics of tic disorders in children and adolescents with the chief complaint of abnormal blinking - Tang, Na; Wang, Yunjiao; Jiang, Xiaohan; Liu, Huan; Li, Yan; Qu, Jia; Xiang, Shengjin (Frontiers in psychiatry, 2025)
Abnormal blinking is a common symptom shared by allergic conjunctivitis (AC), dry eye disease (DED), and tic disorders (TD). This study explored clinical manifestations of TD in patients with the chief complaint of abnormal blinking; its goal was to reduce misdiagnosis and missed diagnosis. In total, 1054 patients with the chief complaint of abnormal blinking completed a questionnaire and underwent comprehensive ophthalmic examinations and mental health assessments. Questionnaire data were compiled for patients with a confirmed diagnosis of TD; their clinical characteristics were analyzed. Of the 1054 patients presenting with abnormal blinking, 453 (42.98%) were diagnosed with a TD. Among these 453 patients, 253 (55.63%) had provisional tic disorder (PTD). 121 (26.71%) patients initially were misdiagnosed (primarily with AC) or experienced a missed diagnosis; Patients with PTD were more likely to seek ophthalmologic care, whereas those with CTD or TS were more likely to visit a paediatrician (P<0.001). The predominant eye tics were excessive and/or frequent blinking; 438 (96.69%) patients exhibited tics other than eye tics. Among the TD patients, 371 (81.90%) reported ocular symptoms, whereas 336 (74.17%) had comorbid eye diseases including AC and DED. PTD patients with AC had higher incidences of allergic rhinitis and asthma compared with patients displaying CTD and TS (P<0.05). TD are major causes of abnormal blinking, and PTD is the most common subtype. TD patients with abnormal blinking often have comorbid eye diseases, primarily AC and DED.